Tingkat Kepuasan Konsumen Di Tempat Wisata Melby’LS Kota Tomohon - Kundrat, Pungus; Memah, Melsje Yellie; Baroleh, Jenny (AGRI-SOSIOEKONOMI, 2023)
This study aims to analyze the level of consumer satisfaction at tourist attractions Melby'LS Tomohon City. This research was conducted in September 2022. The data used in this research consisted of primary data and secondary data. Primary data was obtained through direct interviews with 50 respondents using a questionnaire. Secondary data was obtained through tour owners, the internet and other sources related to this research. The results showed that the level of consumer satisfaction at the Melby'LS tourist spot from the product, price, service and emotional variables was 74.43% of the consumers at the Melby'LS tourist spot were satisfied (P) with the product, price, service and emotion applied.